Research on Price Discrimination Behavior Governance of E-Commerce Platforms—A Bayesian Game Model Based on the Right to Data Portability - Jing Yu; Wensheng Jia (Axioms, 2023)
The behavior of e-commerce platforms using big data algorithms to implement “big data killing” is not only rejected by regular customers, but also creates many difficulties for supervision by relevant government departments. In order to study how to curb the price discrimination behavior of e-commerce platforms in the case of taking regular customers as the leaders, this paper introduces the right to data portability and considers two types of regular customers with high price sensitivity and low price sensitivity. Then, we build a Bayesian game model between e-commerce platforms and regular customers on the basis of the established general game model. Our experiments show that when the reuse value coefficient of personal data is high, the e-commerce platform will choose a uniform pricing strategy, which indicates that the right to data portability can curb the price discrimination behavior of the e-commerce platform to a certain extent. Moreover, when the proportion of high-sensitivity consumers among regular customers increases, e-commerce platforms will be prompted to choose the uniform pricing strategy, which indicates that consumers can curb price discrimination behaviour on e-commerce platforms by increasing their sensitivity for price change.